Lithography process control - Levinson, Harry J. (SPIE Optical Engineering Press, 1999)
This text covers lithography process control at several levels, from fundamental through advanced topics. The book is a self-contained tutorial that works both as an introduction to the technology and as a reference for the experienced lithographer. It reviews the foundations of statistical process control as background for advanced topics such as complex processes and feedback. In addition, it presents control methodologies that may be applied to process development pilot lines.
Keywords: Semiconductors -- Etching.; Microlithography -- Quality control.; elektronické knihy; electronic books